+0  
 
0
328
1
avatar

when dividing by x-1 x+2 x-2 x-3 the polynomial p(x)=x^4+ax^3+bx^2+c+d remainder 0

Guest Jul 25, 2017
 #1
avatar+9653 
+1

Do you mean p(x)=x^4+ax^3+bx^2+cx+d ???

 

(x-1)*( x+2)*( x-2)*( x-3)=x4-4x3-1x2+16x-12

 

a=-4  b=-1   c=16   d=-12

 

laugh

Omi67  Jul 25, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.